Moving your library getting the collection from here to there - Fortriede, Steven Carl (IG library, 2010)
Author and experienced mover Steven Carl Fortriede has everything you need to get the job done quickly and efficiently with step-by-step directions, diagrams, spreadsheets, and photos.